The role of sentinel lymph nodes in endometrial and cervical cancer. Issue 7 (9th September 2015) - Smith, Blair; Backes, Floor
Abstract : Sentinel lymph node assessment aims to determine lymphatic spread while preventing unnecessary interventions and morbidity for those who will not benefit from lymphadenectomy. All detection methods have demonstrated reasonable sensitivity with a low false negative rate and high negative predictive value; as long as the surgeon removes all enlarged lymph nodes and a site‐specific lymphadenectomy is performed if there is no mapping. The significance of micrometastases and long term outcomes are yet to be determined. J. Surg. Oncol. 2015;112:753–760 . © 2015 Wiley Periodicals, Inc.